Mucositis in head and neck cancer patients treated with radiotherapy and systemic therapies: Literature review and consensus statements. (April 2016) - De Sanctis, Vitaliana; Bossi, Paolo; Sanguineti, Giuseppe; Trippa, Fabio; Ferrari, Daris; Bacigalupo, Almalina; Ripamonti, Carla Ida; Buglione, Michela; Pergolizzi, Stefano; Langendjik, Johannes A.; Murphy, Barbara; Raber-Durlacher, Judith; et al.
Highlights: 13 clusters of statements had consensus from a multidisciplinary international expert panel on the management of oral mucositis (OM) in head and neck cancer patients (HNCPs). Before chemo-radiotherapy: general statements, risk factors, assessment tools and preventive hygiene of oral cavity. During chemo-radiotherapy: statements about recommended, no recommended, suggested and no-suggested practice to manage OM in HNCPs. Statements about the radiotherapic precautions to be adopted in order toreduce the risk of radioinduced OM in HNCPs. Abstract: Background: Oral mucositis (OM) due to radiotherapy and systemic therapies in head and neck cancer treatment represents a major problem causing a wide spectrum of clinical signs and symptoms. This adverse event may reduce quality of life, resulting from debilitating oral pain, bleeding, dysphagia, infections, impairment of food intake, high rate of hospitalization and may interfere with the delivery of programmed treatment plans, ultimately jeopardizing patient outcome. Globally, there is a lack of evidence on effective measures for the prevention and treatment of OM, and only scant uniform conclusions and recommendations can be derived from the existing literature and guidelines. A multidisciplinary team of Italian head and neck cancer experts met in Milan 17–18 February 2013 with the aim of reaching consensus on prophylaxis and management of mucositis. The results of the literature review and the statements that achieved consensus are reported and discussed in this paper. Material and methods: The Delphi Appropriateness Method was used as a structured communication method for achieving consensus. Subsequently, external expert reviewers evaluated the conclusions carefully according to their area of expertise. Results: This paper presents 13 clusters of statements on prophylaxis and treatment of mucositis that achieved consensus. Conclusions: OM represents a very stressfull situation for head and neck cancer patients submitted to chemo-radiation or exclusive radiation treatment. A multidisciplinary approach is mandatory, but there is still no gold-standard protocol that is prominently better than others.